'Voices' from the UNTAC Files: Policy and Politics of Accommodation in Phnom Penh after the Khmer Rouge. (September 2015) - Kolnberger, Thomas
During the 1980s, refugee camps along the Thai–Cambodian border constituted the power base for the civil war parties opposing the People's Republic of Kampuchea (PRK, 1979–91). Politics of accommodation and basic services also played a key role in the 'original accumulation' of political power by the new regime in Phnom Penh. The resettlement process of Cambodia's deserted cities developed into a major playground for clientelism, the foundation of Cambodia's state-building process after the Khmer Rouge. Focusing on the archival heritage of the United Nations Transitional Authority in Cambodia (UNTAC) 1992–93, a spatial analysis of Phnom Penh's political geography from the late 1970s to the late 1990s will be provided. This paper argues that the UNTAC time marked a watershed, whose impact has been underrated for Cambodia's political future: the transition in the accommodation policy of a besieged regime. UNTAC did not end the civil war, but changed the political economy of the country. As the need to 'camp-in' and share billeted living space gradually diminished, the socialist 'moral economy' mutated into quick money politics and political family business to ensure the hegemonic status of Cambodia's ruling party further.